2021
DOI: 10.1039/d0fo02878a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of almond intake on lipid profile: a systematic review and meta-analysis of randomized controlled trials

Abstract: A number of clinical trials have examined the effect of almond intake on lipid profile in recent years; however, the results remain equivocal. Therefore, the present study aims to summarize...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 62 publications
1
28
1
2
Order By: Relevance
“…In contrast with our findings, Asbaghi et al, in a meta‐analysis of 27 RCTs, revealed that almond intake significantly changed the serum concentrations of TG, TC, and LDL‐C among healthy and unhealthy people (Asbaghi et al, 2021). However, in line with our findings, in a systematic review and meta‐analysis conducted by Lee‐Bravatti et al, they reported that almond consumption caused a significant decrease in serum LDL‐C concentration; however, TG concentration was not significantly different (Lee‐Bravatti et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast with our findings, Asbaghi et al, in a meta‐analysis of 27 RCTs, revealed that almond intake significantly changed the serum concentrations of TG, TC, and LDL‐C among healthy and unhealthy people (Asbaghi et al, 2021). However, in line with our findings, in a systematic review and meta‐analysis conducted by Lee‐Bravatti et al, they reported that almond consumption caused a significant decrease in serum LDL‐C concentration; however, TG concentration was not significantly different (Lee‐Bravatti et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…However, in line with our findings, in a systematic review and meta-analysis conducted by Lee-Bravatti et al, they reported that almond consumption caused a significant decrease in serum LDL-C concentration; however, TG concentration was not One of the reasons for this discrepancy could be the difference in the type of population studied. The studies included in this metaanalysis were all designed for patients with diabetes, a significant percentage of whom also have dyslipidemia, while in the previous metaanalysis (Asbaghi, Moodi, et al, 2021;Musa-Veloso, Paulionis, Poon, & Lee, 2016), participants with different health status were included in the analysis. Almonds contain some active ingredients such as monoand polyunsaturated fatty acids (particularly conjugated linoleic acids), which can improve lipid profile.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, non-alcoholic beverages; desserts; candy, sugar, and sweets were partially displaced by walnuts. These types of foods might be associated with weight gain [ 26 , 27 , 28 ], reduced bone strength [ 29 , 30 ], nutritional deficiencies [ 29 , 30 ], dental caries [ 31 , 32 ], hypertension [ 3 , 5 , 14 , 33 ], type 2 diabetes [ 28 , 34 , 35 ], cardiovascular disease [ 3 , 5 , 12 , 13 , 14 ], metabolic syndrome [ 27 ], and non-alcoholic fatty liver disease [ 36 ]. Walnuts displaced seven food groups by more than 110%, which means that participants ate less of these food groups in the walnut-supplemented diet than in the habitual diet.…”
Section: Discussionmentioning
confidence: 99%
“…Several large epidemiological studies have proven the protective effects of nut consumption on cardiovascular health [ 9 , 10 , 11 ] and blood lipid profiles [ 5 , 12 , 13 , 14 , 15 ], and in preventing cardiovascular disease complications and early death among individuals with type 2 diabetes [ 16 , 17 ]. Although considered a dense source of energy due to their fat content, regular nut consumption has not been implicated in long-term weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…The lipid effects for individual nut types have been examined in meta-analyses of RCTs using walnuts (24 studies) [ 70 ], almonds (27 studies) [ 71 ], pistachios (11 studies) [ 72 ], hazelnuts (3 studies) [ 73 ], and cashews (3 studies) [ 74 ]. All individual nuts except cashews reduced LDL-cholesterol to a similar extent than reported for total nuts in the mentioned systematic reviews [ 9 , 67 ], but cashews had no effect, which may be due to the low number of RCTs analyzed.…”
Section: Nut Consumption and Health Outcomesmentioning
confidence: 99%